2018
DOI: 10.1007/s11032-018-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing theVrs1 gene in Spanish barley landraces revealed reversion of six-rowed to two-rowed spike

Abstract: Six-rowed spike 1 (Vrs1) is a gene of major importance for barley breeding and germplasm management as is the main gene determining spike row-type (2-rowed vs 6-rowed). This is a widely used DUS trait, and has been often associated to phenotypic traits beyond spike type. Comprehensive re-sequencing Vrs1 revealed three two-rowed alleles (Vrs1.b2; Vrs1.b3; Vrs1.t1) and four six-rowed (vrs1.a1; vrs1.a2; vrs1.a3; vrs1.a4) in the natural population. However, the current knowledge about Vrs1 alleles and its distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…First, the germplasm groups arriving in the Peninsula prevailed in areas where they found appropriate niches. These groups then hybridized with each other to some extent in boundary regions, and evolved locally through mutations (Casas et al, ) and recombination, therefore producing new alleles and new allelic combinations that may have provided more ground for adaptation and selection. In fact, barley landraces from Spain are far from homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…First, the germplasm groups arriving in the Peninsula prevailed in areas where they found appropriate niches. These groups then hybridized with each other to some extent in boundary regions, and evolved locally through mutations (Casas et al, ) and recombination, therefore producing new alleles and new allelic combinations that may have provided more ground for adaptation and selection. In fact, barley landraces from Spain are far from homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…(2020a) reported on the development and characterization of numerous Rph introgression lines in cultivar Bowman (BW lines). With 20 different haplotype patterns in the 50 BW lines likely to have the Rph15 resistance allele, the marker diversity near the Rph15 allele is greater than that observed for mutant genes that involved during or after domestication of barley such as non‐brittle rachis ( btr1 and btr2 ) (Casas et al ., 2018) and six‐rowed spike type ( vrs1 ) (Pourkheirandish et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Cultivars carrying the gain‐of‐function deficiens allele produce enlarged grains with an increased TGW. The gain‐of‐function deficiens allele has been predominantly selected in Ethiopia, while the impaired or loss‐of‐function alleles producing the six‐rowed spike phenotype have been selected independently several times (Komatsuda et al ., ; Saisho et al ., ; Casas et al ., ). Currently, the deficiens two‐rowed types dominate UK winter barley grain production; hence, the area being used to grow spring barley is also increasing (Sakuma et al ., ).…”
Section: The Genetic Basis Of Floret Developmentmentioning
confidence: 97%
“…These trends are also observed in barley cultivation elsewhere in Europe, and deficiens types can be found in other important barley‐growing regions, including the US. Furthermore, comprehensive resequencing of Vrs1 among Spanish barley subpopulations revealed that the reversion from a nonfunctional six‐rowed allele to a functional two‐rowed allele ( Vrs1.b5 ) occurred through a single nucleotide insertion (Casas et al ., ). These allelic variations indicate that Vrs1 was a driving force for inflorescence form and row type during barley domestication.…”
Section: The Genetic Basis Of Floret Developmentmentioning
confidence: 97%